Investment plans, innovations and credit market deregulation: Empirical results with the Finnish data - Ilmo Pyyhtiä (Bank of Finland, 1994)
This paper is an extension of earlier studies by the writer on the influence of innovations on investment plans.It examines the effects of a change in the financial market regime on the revision of investment plans.The innovations in economic data were measured with the error terms of the VAR model.The VAR model was estimated to demand, user cost of capital and total labour costs in the manufacturing industry.Innovation terms calculated in this way were added to the OLS model, in which the realized investments of manufacturing firms are explained by survey data on investment plans collected by the Bank of Finland.In the earlier studies of the writer innovations are formed using ARIMA models and survey data.The estimation results confirm the findings of the earlier revision models of investment plans.Unpredicted economic innovations alter investment plans and the signs of the estimated coefficients are the expected ones, positive for demand innovations and negative for capital cost and wage cost innovations.The conclusion drawn is that financial market liberalization has not influenced the revision of investment plans.The parameters of the investment plan model are also stable after financial market liberalization.
URN:NBN:fi:bof-20140807397
Keywords: 330